Definitions of “Mental Disorder” from DSM-III to DSM-5 - Mattia Vacca; Alessandro Mura; Gian Pietro Carrogu; Luca Gaviano; Riccardo Atzori; Donatella R. Petretto (Behavioral Sciences)
The definition of “mental disorder” (MD) is one of the most critical themes throughout the history of psychopathology and in the development of the discipline itself. Despite this theme having been addressed since ancient times, the first explicit and shared definition of MD only appeared in the seventies, soon after the first internationally shared nosographies. In this perspective paper, we focused on the definitions of MD proposed in the various versions of the “Diagnostic and Statistical Manual of Mental Disorders—DSM”, starting from the third edition of 1980. Over about 40 years, in the various versions of the DSM, six definitions of MD were proposed. We discussed the general matrix/structure of those definitions, as well as the main similarities and/or divergences, and some of the specific constructs and approaches used in such definitions. Additionally, we examined some papers that addressed the same topic in a similar manner and discussed the general debate that accompanied the proposal of the various DSM definitions, the significant attention those definitions attracted, and some minor and major criticisms.